1995
DOI: 10.1111/j.1365-2249.1995.tb03656.x
|View full text |Cite
|
Sign up to set email alerts
|

The level of the serum opsonin, mannan-binding protein in HIV-1 antibody-positive patients

Abstract: SUMMARYThe concentrations of mannan-binding protein (MBP) in consecutive samples from 10 HIV* persons were estimated using an ELISA based on polyclonal rahbit anti-MBP. The changes in MBP with time were similar in HIV^ and HIV" persons, and did not appear to be of clinical significance. MBP was determined in a further 70 persons found HIV-1 ^ during a period af 25 years (1984)(1985)(1986). Out of the total of 80 patients, 32 have by now died from AIDS. According to the serum level of MBP the HIV-infected perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 23 publications
(26 reference statements)
5
31
1
1
Order By: Relevance
“…Plasma MBL deficiency and MBL2 genetic variants had no role in HIV disease progression in our study population defined as decrease in CD4 + T cell count and increase in viral load, in accord with other findings (Catano et al, 2008;Nielsen et al, 1995;Senaldi et al, 1995) but in contrast to other reports of a significant association Hundt et al, 2000;Tan et al, 2009;Vallinoto et al, 2008). The studies that showed similar results to ours were done in the USA among those with European origins and African Americans (Catano et al, 2008), UK (Senaldi et al, 1995), and Denmark (Nielsen et al, 1995). Studies that showed contrasting results to ours were done in Denmark , China (Tan et al, 2009), Germany (Hundt et al, 2000), and Brazil (Vallinoto et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Plasma MBL deficiency and MBL2 genetic variants had no role in HIV disease progression in our study population defined as decrease in CD4 + T cell count and increase in viral load, in accord with other findings (Catano et al, 2008;Nielsen et al, 1995;Senaldi et al, 1995) but in contrast to other reports of a significant association Hundt et al, 2000;Tan et al, 2009;Vallinoto et al, 2008). The studies that showed similar results to ours were done in the USA among those with European origins and African Americans (Catano et al, 2008), UK (Senaldi et al, 1995), and Denmark (Nielsen et al, 1995). Studies that showed contrasting results to ours were done in Denmark , China (Tan et al, 2009), Germany (Hundt et al, 2000), and Brazil (Vallinoto et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Available literature on association between MBL deficiency and HIV disease progression is conflicting, with some reporting faster HIV disease progression among those with MBL deficiency Hundt et al, 2000;Tan et al, 2009;Vallinoto et al, 2008) but others have reported no association (Catano et al, 2008;Nielsen et al, 1995;Senaldi et al, 1995). Presence of an association between MBL deficiency and decreased survival in HIV infected people has been reported , but conflictingly others reported increased survival in those with variant MBL2 genotypes and MBL deficient individuals (Maas et al, 1998), where MBL deficiency was reported to confer protection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have verified that MBL deficiency increases susceptibility to HIV-1 infection or affects the process of infection 9,[19][20][21] . In the present study, the comparative analysis of genotype frequencies between the two groups revealed only a slightly higher prevalence of the MBL*O variant in HIV-1-seropositive patients compared to the healthy controls, while the allele and genotype differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a possible predisposition to HIV-1 infection due to the high frequency of HIV-infected subjects carrying the allele L in homozygous form, but no significant differences in the frequencies of alleles, haplotypes or genotypes among HIV-1-infected and uninfected subjects was reported. Nielsen et al (1995) and Pastinen et al (1998) have shown that HIV-1-infected subjects presented lower serum levels of MBL compared to uninfected subjects and, according to Mangano et al (2008), MBL plasma concentration is associated with the rate of AIDS progression when considering vertical transmission of the virus. This model was not supported by Senaldi et al (1999).…”
Section: Discussionmentioning
confidence: 99%